PENGARUH STRATEGI GENIUS LEARNING DAN DISPOSISI MATEMATIS TERHADAP PEMAHAMAN KONSEP KELAS V SEKOLAH DASAR - Feniareny Feniareny (Universitas Negeri Padang, 2017)
This study was aimed at determining: (1) the effect of Genius Learning strategy toward concept understanding compared with conventional; (2) the effect of Genius Learning strategy towards concept understanding with high mathematical disposition compared with conventional; (3) the effect of Genius Learning strategy towards concept understanding with low mathematical disposition compared with conventional; (4) the interaction between learning strategy and mathematical disposition in influencing concept understanding. This study was designed as quasi-experimental research by using a 2 x 2 factorial. The data were obtained by using mathematical disposition questionnairesand concept understanding test. Data were analyzed by using t-test and Anova.The result of the data showed that: (1) understanding of the concepts taught by Genius Learning strategy was higher than conventional; (2) understanding of the concepts with high mathematical disposition taught by Genius Learning was higher than conventional; (3) understanding of the concepts with lower mathematical disposition taught by Genius Learning was higher than conventional; (4) There was no interaction between learning strategies andthemathematical disposition in influencing students’ understanding of the concept.Keywords: Concept Understanding; Mathematical Disposition; Genius Learning